2016
DOI: 10.1016/j.cej.2015.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a continuous microwave processing system for hydrocarbon removal from solids

Abstract: A continuous conveyor-belt processing concept using microwave heating was developed and evaluated. Four hydrocarbon-contaminated soils were used as model feedstocks, and the degree of organic removal was assessed against the power and energy input to the process. The findings of this study at scale (150kg/h) are in direct agreement with data obtained in batch laboratory scale experiments, and show that microwave heating processes are fundamentally scalable. It is shown that there is a trade-off between the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…However, up to this power threshold, it is suggested that the efficiency of the hydro-distillation process of the volatile oils is increased, because the steam distillation/ stripping of the oils in the aqueous phase is more energetic. Heat transfer to the bulk material is also minimized, which has been shown in other similar microwave based oil extraction systems to be a critical factor for the total yield of oil recovered [32].…”
Section: The Effect Of Feed Preparation On the Yield Of Essential Oilmentioning
confidence: 99%
“…However, up to this power threshold, it is suggested that the efficiency of the hydro-distillation process of the volatile oils is increased, because the steam distillation/ stripping of the oils in the aqueous phase is more energetic. Heat transfer to the bulk material is also minimized, which has been shown in other similar microwave based oil extraction systems to be a critical factor for the total yield of oil recovered [32].…”
Section: The Effect Of Feed Preparation On the Yield Of Essential Oilmentioning
confidence: 99%
“…This is dependent on the effective integration of the materials handling system with the applicator (Bradshaw et al, 2007;Buttress et al, 2016;Robinson et al, 2010b;Shang et al, 2006). The presentation of the process material in the applicator is critical to matching the impedance of the load to the transmission line so that power transfer can be optimised and the propensity for the system to generate process arcs in certain systems minimised.…”
Section: Integration Of Materials Handling With Electromagnetic Designmentioning
confidence: 99%
“…Indeed, a lack of data from demonstration plants often prevents successful scale-up because the technical risks have not yet been fully evaluated and mitigated [52].…”
Section: Figurementioning
confidence: 99%
“…They have been evaluated for their electromagnetic compatibility and ability to deliver enough power density to induce pyrolysis without using microwave susceptor additives. Electromagnetic simulations are presented for each concept for heating at 2.45 GHz using a wellestablished procedure [52]. COMSOL Multiphysics® 4.4 has been used to determine the 3D distribution of the electric field (V/m) inside the cavity and within the biomass load, and then to calculate the power density (W/m 3 )…”
Section: Potential Scalable Microwave Pyrolysis Conceptsmentioning
confidence: 99%